The Synergistic Effects of SHR6390 Combined With Pyrotinib on HER2+/HR+ Breast Cancer - Wang, Yukun; Yuan, Xiang; Li, Jing; Liu, Zhiwei; Li, Xinyang; Wang, Ziming; Wei, Limin; Li, Yuanpei; Wang, Xinshuai (Frontiers in Cell and Developmental Biology, 2021)
HER2+/HR+ breast cancer is a special molecular type of breast cancer, the existing treatment methods are prone to resistance. "Precision treatment" is a necessary. Pyrotinib is a pan-her kinase inhibitor that can be used in HER2-positive tumors, while, SHR6390 is a CDK4/6 inhibitor that can inhibit ER+ breast cancer cell cycle progression and cancer cell proliferation. In cancer cells, HER2 and CDK4/6 signaling pathways could be non-redundant, co-inhibition of both pathways by combination of SHR6390 and Pyrotinib may have synergistic anticancer activity on HER2+/HR+ breast cancer. In this study we determined the synergy of the two drugs combination and underlying molecular mechanisms. We showed that the combination of SHR6390 and Pyrotinib synergistically inhibited the proliferation, migration and invasion of HER2+/HR+ breast cancer cells in vitro. The combination of two drugs induced G1/S phase arrest and apoptosis in HER2+/HR+ breast cancer cell lines. The combination of two drugs prolonged the time to tumor recurrence in the xenograft model system. By second-generation RNA sequencing technology and enrichment analysis of Pyrotinib-resistant cell line, we found that FOXM1 was associated with induced resistance to HER2-targeted therapy. In HER2+/HR+ breast cancer cell lines, the combination of the two drugs could further reduce FOXM1 phosphorylation, thereby enhancing the anti-tumor effect to a certain extent. These findings suggest that SHR6390 combination with Pyrotinib suppress the proliferation, migration, and invasion of HER2+/HR+ breast cancers through regulation of the FOXM1.